Obesity As A Risk Factor For Hypertension - Febri Endra Budi Setyawan; Riana Widyastuti; Shandi Andara Putra; Ashifarachma Ekasari; Novianita Anugrah Islami; Nur Hafidhah Fitriani; Lingga Caraka Putri (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2022)
Background: In Baruharjo Public Health Center in Trenggalek, hypertension is ranked 1 as the most common cases in 2021. Based on the results of Riskesdas in 2018, the increase in cases of hypertension in Indonesia is in line with the prevalence of obesity. Method: This study is a Systematic review. 34 journals published at least 5 years ago were acquired. Journals contain the topic of health problems about obesity as a risk factor for hypertension. Result: Through the process of reviewing and selecting articles, researchers obtained 34 journals that matched the inclusion and exclusion criteria, and were relevant to this research. From all the 34 journals that we have reviewed, most of them found a significant relationship between obesity and hypertension. Only 1 journal that showed if there was no relationship between obesity and hypertension, but there is still no further explanation about the reason why there was no relationship between both of them. Discussion: Someone with an overweight/obese BMI is four until eight times more likely to have hypertension than a person with normal BMI. Obesity can cause hypertension through various mechanisms, either directly or indirectly. The pathophysiology of obesity induced hypertension involve activation of the sympathetic nervous system and the RAAS or renin-angiotensin-aldosterone system. In addition, the occurrence of endothelial dysfunction and the abnormalities in kidney function are also important factors in the occurrence of hypertension in obese people. Every 10 percent increase in body weight can increase systolic levels by about 5.6 mmHg. Conclusion: Obesity is strongly associated with hypertension. Losing even a small amount of weight if you're overweight or obese and or controlling your weight can help reduce your blood pressure.